Adding markers of organ damage to risk score models improves cardiovascular risk assessment: Prospective analysis of a large cohort of adult outpatients. (1st December 2017) - Tocci, Giuliano; Figliuzzi, Ilaria; Presta, Vivianne; Attalla El Halabieh, Nadia; Citoni, Barbara; Coluccia, Roberta; Battistoni, Allegra; Ferrucci, Andrea; Volpe, Massimo
Abstract: Introduction: Global cardiovascular (CV) risk stratification is recommended in all outpatients. Risk score charts, however, do not include markers of organ damage (OD). Aim: To evaluate the potential added value of including different markers of subclinical OD to US Framingham, European SCORE and Italian Cuore risk score calculators. Methods: We prospectively evaluated adult outpatients, who underwent blood pressure (BP) assessment and global CV risk stratification. The following OD markers were considered: 1) cardiac OD: electrocardiographic) or echocardiographic left ventricular (LV) hypertrophy; 2) vascular OD: carotid atherosclerotic plaque; 3) renal OD: reduced estimated glomerular filtration rate or creatinine clearance. Different risk score calculators were applied for comparisons. Results: We included an overall population sample of 1979 outpatients (44.0% female, age 57.2 ± 13.0 years, BMI 26, 6 ± 4, 4 kg/m 2, clinic systolic/diastolic BP 145.4 ± 18.3/85.8 ± 10.7 mm Hg), among whom 117 (5.9%) presented cardiac, 161 (8.1%) vascular, and 117 (5.9%) renal OD. US Framingham, European SCORE and Italian Cuore risk scores were all significantly raised in patients with than in those without OD. A trend toward increase for US Framingham CVD death, European ESC and Italian Cuore scores was observed according to degree of all markers of OD. Among these, reduced ClCr and eGFR showed high sensitivity and specificity to identify high risk individuals. Conclusions: Presence of cardiac, vascular or renal OD is associated with higher risk scores, independently by the types of calculators, age and gender classes. OD detection should be included in CV risk stratification in order to improve diagnostic, prognostic and therapeutic processes.